Technology Integration in Flipped Classroom at Science Learning: Insights from a Systematic Literature Review - Tri Wiyoko; Urip Sulistyo; Sofyan; Andriayanto (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
21st century education requires learning that not only transfers knowledge, but also develops critical thinking skills, creativity, collaboration, and digital literacy. The flipped classroom model has emerged as an effective pedagogical innovation to support these goals, especially in science learning. This study aims to identify the research methods and types of technology used in the flipped classroom, how technology is integrated into each phase of learning, and its impact on science learning. This study uses the Systematic Literature Review (SLR) method to analyze articles sourced from the Scopus database from 20216-2025. There are 16 articles that examine the results of research using the flipped classroom. The results show that there was a trend of diverse methods in the application of the flipped classroom in 2019-2020 due to the Covid-19 pandemic. The integration of technology such as learning videos, Learning Management Systems (LMS), gamification, and online-based assessment platforms played a significant role in the implementation of the flipped classroom. The impact of the flipped classroom on science learning can increase student engagement, intrinsic motivation, and understanding of science concepts. Thus, the application of technology in the flipped classroom has proven to be effective in supporting more interactive, flexible, and in-depth learning.